Laparoscopic approach to duodenal obstruction: report of the first 2 cases in Uruguay (Archives of Pediatrics of Uruguay, 2025)
Duodenal atresia is a rare pathology and the first cause of neonatal duodenal obstruction. Its treatment is surgical, and it has evolved over the past 20 years, from conventional to minimally invasive approaches, endoscopic and particularly laparoscopic. In 2022, the first 2 reported cases of laparoscopic management of this condition were performed in Uruguay at the Pereira Rossell Hospital Center. This paper presents the cases involving a 12-day-old newborn and a 7-month-old infant. The procedures were uncomplicated, with early enteral full feeding, minimal postoperative pain and excellent aesthetic results. Laparoscopy proved to be a reproducible technique in newborns and infants, without adding morbidity or mortality and providing additional benefits.
Keywords: Duodenal Obstruction; Intestinal Atresia; Laparoscopy